The Indonesian Terms of Disease Names: A Corpus Linguistic Study - Hernina, Hernina; Karlina, Yenny; Puspitasari, Devi Ambarwati (OKARA: Jurnal Bahasa dan Sastra, 2023)
The Indonesian terms of disease names are unique. Despite being different from their medical terms, Indonesian terms of disease names contain elements of figurative language. This study aims to analyze stylistic naming. The data were Corpora from articles, social media forums, and online news on health for 2013-2023, involving 1.206.281.985 tokens from the Indonesian-Leipzig Corpora Collection (ILC) and 39.294 tokens collected for the 2023 Health Forum Corpus (HF). Data analysis concerned the wordlist and collocation feature to see the frequency, trend, and pattern, and the concordance feature examined the language style of the names. The study does not find any evidence of changes in health terms over the past decade, such as â€œpenyakit jantungâ€ (heart disease), "headache," and "hospital." However, it does uncover some interesting findings regarding the formation of disease names. Affixation and compounding are the primary word formation processes. The stylistic elements of disease names were hyperbolic figures, such as "gagal ginjal" (chronic kidney disease), and symbolic figures, such as "kaki gajah" (filariasis) and "mata ikan" (clavus). In conclusion, the names of diseases followed a particular pattern, but the specific terminology used might vary based on linguistic factors and cultural understanding.